The Adsorption of Cement Superplasticizers on to Mineral Dispersions - A. Pierre; R. Mercier; A. Foissy; J.M. Lamarche (Adsorption Science & Technology)
The adsorption of polymeric sulphonated naphthalene formaldehyde (SNF) and sulphonated melamine formaldehyde (SMF) on to titanium dioxide and calcium carbonate has been measured in aqueous media. The magnitude of these adsorptions is strongly dependent on electrostatic interaction irrespective of the pH value. This result has been established by studying the adsorption of the polyelectrolytes from solutions of different composition. The calcium ion plays a prominent role in the process of adsorption, especially at high pH where electrical interactions do not favour the reaction. The polymeric nature of the fluidizing agents is demonstrated by an increase in adsorption with molecular weight and by adsorption/desorption experiments where the reaction has been shown to be irreversible. The amount adsorbed at maximum coverage does not depend on the nature of the mineral, but mainly on electrical interactions between the monomer units.